CATASTROPHIC FAILURE INVESTIGATION OF THE OIL FILTER MACHINE BOLTS - Gatot Prayogo (Indonesian Journal of Engineering and Science, 2023)
An assessment of the fractured bolt of a cooking oil filter machine was performed. The objective of this assessment is to reveal the root cause of the failure. A series of necessary attempts were carried out for this analysis, i.e., site visit, fracture surface examination of the fractured bolt, collecting the maintenance and operation data, mechanical properties testing, chemical composition testing, and stress analysis. The fracture surface examination showed a catastrophic failure, especially at a repaired bolt. Meanwhile, according to the site visit investigation, some evident data indicated a sudden high-pressure load subjected to the filter machine. Most fractured filter bolts were repaired by welding. The design review shows that the critical operating pressure is around 14.5 bar, which is far above the reported operating pressure during the accident, which is 6 bar. This indicated that the strength of the genuine bolt is sufficient to ensure the operating pressure of the filter machine, which is normally 1 to 3.5 bar. Finally, it can be concluded that the root cause of the failure of the filter machine bolt is decreasing strength of the bolts because of improper repairment indicated by the welding process and assisted by sudden high load due to increasing pressure inside the filter vessel.